THE TRAJECTORIES OF HADITH STUDIES IN INDONESIA (2014-2024) - Lubis, Zainal Abidin; Najwah, Nurun; Haris, Abdul (Journal of Contemporary Islam and Muslim Societies, 2025)
Abstract: This study examines the development of Hadith studies in Indonesia during the period 2014–2024 by analyzing doctoral dissertations from three prominent institutions: UIN Syarif Hidayatullah Jakarta, UIN Sumatera Utara, and UIN Alauddin Makassar. Historically, these universities have been among the earliest providers of doctoral programs in Islamic studies and have played a significant role in shaping the production of Islamic knowledge in Indonesia. The research aims to map the typologies of Hadith studies, the issues addressed, and the methodologies employed. Data were collected through higher education repositories, from which relevant dissertations were identified, cataloged, and analyzed. The findings reveal that, within the studied period, there were 78 dissertations covering diverse topics. The typology shows that 37 dissertations (47.43%) focused on character-based studies, followed by 23 (29.48%) thematic Hadith studies, 10 (12.82%) studies on ‘Ulūm al-Hadīth, and 8 (10.26%) studies on the application of Hadith in everyday life. This distribution reflects the methodological development within the field, although the discourse remains dominated by intellectual-historical approaches and thematic Hadith studies.Keywords: Islamic knowledge, hadith studies, dissertations, State Islamic Universities